(untitled) (Bangladesh Journal of Urology, 2020)
Background: Posterior Urethral Valves (PUV) are one of the most common urological problems having wide clinical implications and the prognosis depends upon the extent of the renal injury inflicted by the time of initiation of intervention and hence earlier the treatment, better the long-term outcome Objectives: To evaluate the outcome of endoscopic fulguration of posterior urethral valves (PUV) in children. Method: A cross-sectional analytical study was carried out on 50 male children with posterior urethral valves (PUV) from January 2011 to December 2012 in Dhaka Medical College Hospital, who were treated with endoscopic fulguration and came for routine follow-up. Results: In this series, median age of patients was 2 years ranging from 1 to 12 years. Approximately half of the patients (46.0%) were 2 years. Sixty four percent presented with poor urinary stream, 38.0% presented with straining during micturition. The most common physical finding was palpable bladder 60.0%, UTI was present in 52.0% cases. Proteinuria was found in 46.0% cases, raised serum creatinine was found in 36.0% cases. Electrolyte imbalance was found in 12.0% of cases. Ultrasonogram of KUB showed severe hydronephrosis in 14.0% cases. Voiding cystourethrogram diagnosed PUV in 92.0% of cases. The follow-up period was 24 months. At the end of final follow-up 3 patients remained incontinent. Urinary tract infections were absent in 52.0% cases. Hydronephrosis disappeared in 30.0% cases. Chronic renal failure developed in 6.0% of cases. End stage renal disease was found zero during the follow-up period. Conclusion: Follow-up period of longer duration needed to determine the ultimate outcome of these patients because some of the patients develop ESRD in the long run and ultimately renal transplant is the treatment. Treatment should be performed in higher centers where all the facilities are available. Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.8-14